Bonsai: an event-based framework for processing and controlling data streams - Lopes, Gonçalo; Bonacchi, Niccolò; Frazão, João; Neto, Joana P.; Atallah, Bassam V.; Soares, Sofia; Moreira, Luís; Matias, Sara; Itskov, Pavel M.; Correia, Patrícia A.; Medina, Roberto E.; Calcaterra, Lorenza; et al. (Frontiers in Neuroinformatics, 2015)
The design of modern scientific experiments requires the control and monitoring of many different data streams. However, the serial execution of programming instructions in a computer makes it a challenge to develop software that can deal with the asynchronous, parallel nature of scientific data. Here we present Bonsai, a modular, high-performance, open-source visual programming framework for the acquisition and online processing of data streams. We describe Bonsai's core principles and architecture and demonstrate how it allows for the rapid and flexible prototyping of integrated experimental designs in neuroscience. We specifically highlight some applications that require the combination of many different hardware and software components, including video tracking of behavior, electrophysiology and closed-loop control of stimulation.